2016
DOI: 10.1371/journal.pone.0168567
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Properties of the Enaminone E121 in the Dextran Sulfate Sodium (DSS) Colitis Model

Abstract: BackgroundEnaminones are synthetic compounds with an established role in the prevention of various forms of seizures. Recent evidence suggests potent anti-tussive, bronchodilation and anti-inflammatory properties. Pre-treatment with particularly E121 compound resulted in a decrease in leukocyte recruitment in the ovalbumin induced-model of asthma, immune cell proliferation and cytokine release in vitro. We hypothesize that E121 might serve as a therapeutic potential in intestinal inflammation through modulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…Bcl-2 is regarded as a prosurvival molecule, whereas Bax is a proapoptotic molecule as it binds to and antagonizes the effects of Bcl-2 [ 42 ]. Thus, Caspase-3 activation is an important event in cell death [ 43 ]. SCB showed substantial downregulation of proapoptotic genes, such as Bax and Caspase-3 ( P < 0.001 and P < 0.05, resp.).…”
Section: Resultsmentioning
confidence: 99%
“…Bcl-2 is regarded as a prosurvival molecule, whereas Bax is a proapoptotic molecule as it binds to and antagonizes the effects of Bcl-2 [ 42 ]. Thus, Caspase-3 activation is an important event in cell death [ 43 ]. SCB showed substantial downregulation of proapoptotic genes, such as Bax and Caspase-3 ( P < 0.001 and P < 0.05, resp.).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the enhanced total and phosphorylated form of AKT in the colon of DSS‐treated mice were reduced back to expression control levels by E121 treatment, and the enhanced colonic expression levels of p‐ERK1/2 and p38 MAPK post‐DSS treatment were reduced to control levels by E121 treatment. Thus, evidence was shown that the anti‐inflammatory property of E121 is in part mediated through modulating the activity of pro‐inflammatory signalling pathways, colonic epithelial cell apoptosis, neutrophil apoptosis, chemotaxis and superoxide release . Given its potential to decrease pro‐inflammatory cytokines such as TNF‐alpha and IL‐6 in vitro as well as in vivo , E121 may play a role in mitigating cytokines in IBD or RA, without the same adverse effects as glucocorticoids, given their structural differences.…”
Section: Novel Drug Targetsmentioning
confidence: 99%
“…Further, results indicate that E121 is able to suppress the release of proinflammatory cytokines TNF-alpha and IL-6, as well as moderately decrease total nitric oxide after stimulation with LPS, but not IFN-gamma, indicating that there is a target for this compound in the TLR4 signalling pathway, potentially p38 MAPK. [42] Studies of p38 MAPK inhibition alongside glucocorticoid treatment have suggested that inhibiting p38 can possibly increase glucocorticoid effectiveness by increasing GR nuclear translocation. [43,44] Thus, inhibiting kinases may increase the efficacy of the glucocorticoid in decreasing pro-inflammatory cytokine release.…”
Section: Signalling Targetsmentioning
confidence: 99%
See 2 more Smart Citations